The dynamics of the regulation of labor in developing and developed countries since 1960 - Nauro F. Campos; Jeffrey B. Nugent (Institute for the Study of Labor (IZA), 2012)
This paper examines both the determinants and the effects of changes in the rigidity of labor market legislation across countries over time. Recent research identifies the origin of the legal system as being a major determinant of the cross-country variation in the rigidity of employment protection legislation. However, the supporting evidence is largely confined to levels of regulation and is almost exclusively based on international cross-section data for the post-1995 period. This paper introduces a new index capturing the rigidity of employment protection legislation (LAMRIG) for an unbalanced panel of more than 140 countries over time starting in 1960. Although the importance of legal origins in explaining the level of rigidity of labor regulations across countries is replicated using LAMRIG, their explanatory power is much weakened for changes over time (1960-2004.) More important as determinants of such changes are the level of development and other reforms such as trade liberalization. With respect to the effects of changes in the rigidity of labor regulations on growth and inequality, which have been very controversial in the literature, results with LAMRIG support Freeman's conjecture that changes in rigidity do not systematically affect economic growth but do lower income inequality.
Keywords: J41; J65; J33; K31; O21; 330; employment protection legislation; labor market institutions; reforms; Arbeitnehmerschutz; Arbeitsrecht; Arbeitsmarktflexibilität; Wirtschaftswachstum; Einkommensverteilung; Welt; Industriestaaten; Entwicklungsländer